Extraction and characterization of milkfish (Chanos chanos) - Morados, Franzel Mae A.
The study was conducted to (1) determine the extraction temperature of gelatin from Milkfish bone that will provide the highest gel strength, (2) determine selected physico-chemical properties to characterize the gelatin with the highest gel strength, and (3) compare the obtained results against commercial gelatin. The extraction temperature that yielded the highest gel strength from the extracted gelatin of Milkfish bone at 55oC (44.43 g) was not significantly different from the gel strength of commercial gelatin (53.93 g). The milkfish bone gelatin has protein content, ash content, and moisture content of 38.01%, 0.53%, and 21.46%, respectively; while the commercial gelatin has 79.44%, 0.90%, and 14.83%, respectively. The protein and ash content of the extracted gelatin were found to be significantly lower that the commercial gelatin. However, the moisture content of Milkfish bone gelatin was higher than commercial gelatin. On the other hand, the melting temperature, gel clarity, viscosity, ph, and gel color of the extracted Milkfish bone gelatin extracted at 55oC were 22oC, 29.30%, 1.27-1.50 cP, ph 3.27, and L*=64.31, a* = -2.24, and b*=14.99, respectively. These values determined were significantly lower than the commercial gelatin which were 30oC, 68.23%, 2.30-2.40 cP, pH 6.18, (L*) 62.80, (a*) -2.17, (b*) 22.31, respectively.